Work Place Factors Contributing To Stress Among University Teachers And Coping Strategies: A Study Of Tamale Technical University - Jakku, Simon Yahaya; Manja , Ernest Kipo; Ba –an, Maxwell Tengolzor (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
Workplace stress is a worldwide problem. Aside from teaching, university instructors have numerous other responsibilities and are always stressed. The study’s goal was to investigate the effects of stress on staff performance at Tamale Technical University. To analyze the issue, a qualitative case study methodology was used. Purposive sampling was used to conduct semi-structured interviews with 20 university lecturers. Thematic analysis was used to examine the acquired data. Workplace stress has a detrimental influence on employee performance, according to the findings. This study was done on tertiary education level employees at Tamale Technical University, which is located in the Northern Regional Capital Tamale. As a result, the research might be limited to a single place. However, this study is crucial in order to retain highly valued university staff. An attempt was made to identify job stress mitigation measures that individuals and employers may use to overcome job stress and increase performance. Management can take the required actions to control workers’ workplace stress levels in order to improve their job performance. They may offer counseling, a meditation program, incentives, and other benefits that increase employee performance over time.